206k views
6 votes
Solve:
2x + y = 11
x + 3y = 3

User Kaze
by
4.6k points

1 Answer

5 votes

Answer:

Explanation:

Here you go mate

Step 1

2x + y = 11 and x + 3y = 3 Equation/Question

Step 2

x+3y=3 Substitute -2x+11 for y

x+3(-2x+11)=3

Step 3

x+3(-2x+11)=3 simplify

x=6

Step 4

y=-2x+11 Substitute 6 for x

y=-2(6)+11

Step 5

y=-2(6)+11 simplify

y=-1

answer

x=6

y=-1........hope this helps

User MHammer
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.